Amino-functionalized hydrogel immobilized microbial consortia to reduce the dissemination risks of antibiotic resistance genes in soil - Yongxin Guo; Jiaoyang Ji; Xianfeng Lin; Yanjun Li; Gang Wang; Yong Yu (Bioresource Technology, 2026)

Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Optimization of zeotropic series cycle for improved temperature matching and energy efficiency in compact household refrigerators - Bingqi Li; Yanjun Du; Xudong Ma; Yuting Wu; Che Wang; Jie Lin; Haiqing Guan; Lubing Wang (International Journal of Refrigeration, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

Co-fermentation of kombucha-derived yeasts and Komagataeibacter hansenii: Effects on polyphenol composition and flavor profiles - Yanjun Wei; Yingxi Chen; Yiwei Dai; Xinping Lin; Beiwei Zhu; Chaofan Ji (Food Bioscience, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Distinct patterns of intestinal microbiota and immune responses under acute and chronic ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Kun Xiao; Liling Nie; Shasha Zhao; Gehan Gao; Cuancheng Zhao; Yanjun Du; Rongfei Hu; Ruru Lin; Jie Wang; Man Wang; Dong Han; Lei Zhang (Aquaculture, 2026)

Impact of meteorological factors on other infectious diarrhea in mainland China: comprehensive risk assessment, forecasting and early warning - Qiang Hao; Baofa Jiang; Yanjun Wang; Xiaodong Zhang; Lin Zhang (Journal of Environmental Management, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Photo-driven multifunctional membrane evaporator based on Sb2Se3/MoSe2/Ag@PAM for freshwater harvesting and electricity generation - Qiang Zhang; Peiyuan Liu; Zhiwei Yang; Yanjun Liang; Jian Zhang; Lin Wang; Xiao Huang (Chemical Engineering Journal, 2026)

Dauricine ameliorates intestinal inflammation and oxidative stress in DSS-induced colitis through TLR4/NLRP3/GSDMD-mediated pyroptosis and Nrf2 pathway - Lin Wang; Jingyuan Liu; Jiayi Wang; Yuxin Xie; Yanan Gao; Daili Xu; Jing Li; Jing Dong; Bingyao Li; Yanjun Cao; Yang Li; Jiao He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Optimisation study of a geometric-VOF model based on elementary symmetric polynomial and adaptive time-step Crank-Nicolson method - Ziming Xu; Yanjun Liu; Zaibin Lin; Shuting Huang; Hao Chen; Gang Xue (Ocean Engineering, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

An eco-friendly Pickering emulsion gel loading white mustard essential oil for attract-and-kill control of Plutella xylostella larvae - Meng Xiao; Xirui Chen; Xiaoqin Zhao; Qiuxia Li; Chaoyi Peng; Xiaozhuo Chen; Yanjun Lin; Jingjing Li; Jinming Zhang (Chemical Engineering Journal, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

The impact of storage conditions on quality and shelf life of fresh-cut jackfruit: a metabolomics perspective - Yuting Huang; Wenli Zhang; Wanqing Sun; Wenzhu Shen; Yifan Cheng; Yining Xia; Yanjun Zhang; Qiong Lin (Food Chemistry, 2026)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Observation-constrained long-term simulations of water dynamics and groundwater recharge under intensive agriculture in the North China Plain - Lin Wu; Leilei Min; Meiying Liu; Wolfgang Kinzelbach; Shiqing Wang; Ahmed Mady; Yanjun Shen (Groundwater for Sustainable Development, 2025)

CFD simulation of multifluid mixing and structure optimization of rotating liquid film reactor for magnesium hydroxide production - Wenwen Lin; Jiahao Wan; Yingying Zhang; Wenyan Liu; Kaitao Li; Xiongzhong Yan; Jicang Li; Shengting Li; Wendi Liu; Yanjun Lin (Chemical Engineering Journal, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Acid-resistant microporous polyether nanofiltration membrane with high permeability for wastewater treatment - Chuanqi Zhang; Yanjun Zeng; Dan Lu; Yuxin Tao; Zhikan Yao; Saisai Lin; Yunlong Cui; Lin Zhang (Chemical Engineering Journal, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Ascovirus suppresses feeding and growth in Spodoptera litura larvae by targeting the neuropeptide F - Wei Lin; Yanjun Gao; Qiaodi Wang; Zhengkun Xiao; Guo-Hua Huang (Journal of Asia-Pacific Entomology, 2025)

Integrated transcriptome and proteome analysis unveils black tea polyphenols metabolic pathways in Saccharomyces cerevisiae - Yanjun Wei; Yingxi Chen; Xinping Lin; Sufang Zhang; Beiwei Zhu; Chaofan Ji (Food Microbiology, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

High-entropy perovskite embedded in carbon-based catalyst toward peroxymonosulfate activation to degrade Rhodamine B: Performance and mechanism insights - Zihao Chen; Xingqi Huang; Yanjun Zuo; Haibo Wang; Wenming Chen; Lingce Kong; Xiaoyan Lin (Water Research, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Preparation, characterization and antimicrobial properties of double lysine-modified chitosan and its preservation ability in chicken meat refrigeration - Bin Dong; Yijie Wang; Lili Han; Guirong Cui; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Chemistry, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Melatonin attenuates inflammatory bone loss by alleviating mitophagy and lactate production - Zexin Lin; Yuan Gu; Yingsong Liu; Zilin Chen; Shuai Fang; Zhuan Wang; Zixian Liu; Qingrong Lin; Yanjun Hu; Nan Jiang; Bin Yu; Guanqiao Liu (Apoptosis, 2025)

AGSPNet: A framework for parcel-scale crop fine-grained semantic change detection from UAV high-resolution imagery with agricultural geographic scene constraints - Yanjun Wang; Shaochun Li; Hengfan Cai; Lina Deng; Yunhao Lin (Computers and Electronics in Agriculture, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Light regulates seed dormancy through FHY3-mediated activation of ACC OXIDASE 1 in Arabidopsis - Yitong Liu; Shuangrong Liu; Yanjun Jing; Jialong Li; Rongcheng Lin (Plant Molecular Biology, 2025)

Years of life lost attributable to air pollution, a health risk-based air quality index approach in Ningbo, China - Qiang Hao; Lin Zhang; Xiaodong Zhang; Yanjun Wang; Cuixian Zhang; Suyan Meng; Jinhua Xu; Lina Hao; Xia Zhang (International Journal of Biometeorology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

A novel machine learning approach for reservoir temperature prediction - Haoxin Shi; Yanjun Zhang; Yuxiang Cheng; Jixiang Guo; Jianqiao Zheng; Xin Zhang; Yude Lei; Yongjie Ma; Lin Bai (Geothermics, 2025)

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Evaluating and locating a suitable bedrock drilling site near zhongshan station with airborne and ground-based observations - Yanjun Li; Xiangbin Cui; Gang Qiao; Lin Li; Shinan Lang (Polar Science, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

New insight into catalytic performance and reaction mechanism for butyl acetate over CeO2 catalysts: Oxygen vacancy and surface reactive oxygen species - Jiajia Lin; Wenjing Kong; Chuying Qiu; Xueyun Zhong; Yanjun Li; Mingli Fu; Zhenguo Li (Journal of Environmental Chemical Engineering, 2024)

Deficit irrigation combined with a high planting density optimizes root and soil water–nitrogen distribution to enhance cotton productivity in arid regions - Fengquan Wu; Qiuxiang Tang; Jianping Cui; Liwen Tian; Rensong Guo; Liang Wang; Zipiao Zheng; Na Zhang; Yanjun Zhang; Tao Lin (Field Crops Research, 2024)

Chemical fertilizers promote dissemination of ARGs in maize rhizosphere: An overlooked risk revealed after 37-year traditional agriculture practice - Xiaolong Lin; Guanghui Xu; Yanjun Li; Yong Yu (Science of The Total Environment, 2024)

Variation of nitrate sources affected by precipitation with different intensities in groundwater in the piedmont plain area of alluvial-pluvial fan - Heping Sun; Wenbo Zheng; Shiqin Wang; Lin Ma; Leilei Min; Yanjun Shen (Journal of Environmental Management, 2024)

In vitro antimicrobial activity of the novel antimicrobial peptide mytimacin-4 and its influence on the microbial community and quality of pork during refrigerated storage - Bin Dong; Yijie Wang; Guirong Cui; Yuna Wang; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Control, 2024)

Effectiveness of government subsidies for biomass-based industries: Incorporating the feedstock acquisition process - Jun Lin; Yanan Li; Yanjun Qian; Guoquan Liu (Energy Policy, 2024)

Production of cleavage-resistant phytase transgenic pigs by handmade cloning - Mingyuan Zhang; Jun Zhang; Haowen Yang; Shijin Chen; Xiaoliang Chen; Yuemeng Huang; Baojian Chen; Yanjun Wu; Qinyang Jiang; Yafen Guo; Yingming Wei; Xiukun Lin; et al. (Theriogenology, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

Design and Analysis of a Buoy-Based Cable Seafloor Observatory System Response under Extreme Weather Conditions - Wenjie Zhou; Yanjun Li; Yulu Zhang; Qingyan Jiang; Dong Chen; Yanzhen Gu; Yuan Lin (Journal of Marine Science and Engineering, 2024)
In order to address the requirements of scientific multidisciplinary observation in diverse small-scale regions, we have introduced the Buoy-based Cable Seafloor Observatory System (BCSOS). This system offers a distinct advantage in contexts where the use of shorter cables is feasible, contrasting with the lengthy cables typically necessary for conventional observatories. The BCSOS consists of three primary components: the Real-Time Electric Communication (RTEC) Buoy, the Power Information Transmission System (PITS), and the Seafloor Observation Subsystem (SOS). The RTEC Buoy is equipped with instruments for measuring sea surface parameters and serves as a data and power hub. The PITS, comprising a robust EM cable, connects the buoy to the SOS, which houses instruments for seafloor observations. The system is designed for a maximum water depth of 100 m and has an expected lifespan of about 5 years. The BCSOS prototypes were deployed at the Huangqi Peninsula, Fujian Province, and successfully documented the process during Typhoon Doksuri (international code 2305) at the end of July 2023. The recorded data from the BCSOS revealed a significant increase in wave height and period as the storm approached the Huangqi Peninsula. Additionally, the RTEC buoy exhibited a notable response to the large waves. The data analysis revealed a distinct pattern between the buoy response and the direction of wave propagation across various sea conditions, that the buoy’s angular movement in pitch and roll directions follows a regular elliptical distribution corresponding to different wave propagation directions. Upon thorough evaluation, future enhancements to the system are slated to concentrate on refining its design, with a particular emphasis on bolstering stability and enhancing corrosion resistance. These improvements are aimed at cementing the system’s long-term viability and performance within the challenging marine environment.

Associations between per- and polyfluoroalkyl substances exposure and thyroid hormone levels in the elderly - Kai Tan; QingQuan Zhang; Yanjun Wang; Chunfang Wang; Chongfang Hu; Lin Wang; Hualin Liu; Zhiqiang Tian (Science of The Total Environment, 2024)

3D/2D MnO/MXene heterostructure with high efficiency for adsorbing uranium - Chao Zhang; Yi Wang; Yi-Lin Liu; Qingming Zeng; Yanjun Wen; Lulin Guo; Haodong Chen; Xinyi Xie; Qingyi Zeng (Chemical Engineering Journal, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

A self-driven solar coupling system with TiO2@MXene cathode for effectively eliminating uranium and organics from complex wastewater accompanying with electricity generation - Lulin Guo; Yi-Lin Liu; Qingming Zeng; Chao Zhang; Yanjun Wen; Qingyan Zhang; Guolong Tang; Qingsong Zhang; Qingyi Zeng (Journal of Hazardous Materials, 2024)

Ethylene thiourea exposure induces neurobehavioral toxicity in zebrafish by disrupting axon growth and neuromuscular junctions - Jingming Wang; Zhiquan Yu; Yongfeng Wang; Yuanyao Chen; Lin Xiao; Yanjun Zong; Qiyuan Feng; Lianqi Peng; Huiping Zhang; Chunyan Liu (Journal of Environmental Sciences, 2024)

Start-up characteristics of a R290 rotary compressor for an air source heat pump under low ambient temperature condition - Ying Zhao; Yanjun Du; Jie Lin; Nini Guo; Jianhua Wu (International Journal of Refrigeration, 2024)

Effects and mechanisms of polystyrene micro- and nano-plastics on the spread of antibiotic resistance genes from soil to lettuce - Guanghui Xu; Yanjun Li; Xiaolong Lin; Yong Yu (Science of The Total Environment, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Toxic effects and mechanisms of engineered nanoparticles and nanoplastics on lettuce (Lactuca sativa L.) - Yanjun Li; Xiaolong Lin; Guanghui Xu; Qiuliang Yan; Yong Yu (Science of The Total Environment, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Mass-based trophic transfer of polystyrene nanoplastics in the lettuce-snail food chain - Yanjun Li; Xiaolong Lin; Jian Wang; Guanghui Xu; Yong Yu (Science of The Total Environment, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

ROS-activated selective fluorescence imaging of cancer cells via the typical LDH-based nanozyme - Zhengdi Wang; Jiancheng Liu; Min Feng; Kai Song; Kaitao Li; Wendi Liu; Shanyue Guan; Yanjun Lin (Chemical Engineering Journal, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Study on the Law of Fracture Development in Plasma-Induced Broken Coal - Yanjun Li; Baiquan Lin; Xiangliang Zhang; Minghua Lin (Rock Mechanics and Rock Engineering, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

Projected land use changes in the Qinghai-Tibet Plateau at the carbon peak and carbon neutrality targets - Runhong Xu; Peijun Shi; Miaoni Gao; Yanjun Wang; Guojie Wang; Buda Su; Jinlong Huang; Qigen Lin; Tong Jiang (Science China Earth Sciences, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Environmental-friendly and effectively regenerate anode material of spent lithium-ion batteries into high-performance P-doped graphite - Xiuying Yang; Honggang Zhen; Haozhou Liu; Chaojiu Chen; Yanjun Zhong; Xiushan Yang; Xinlong Wang; Lin Yang (Waste Management, 2023)

Meeting the heavy-metal safety requirements for food crops by using biochar: An investigation using sunflower as a representative plant under different atmospheric CO2 concentrations - Yiying Wang; Guiying Lin; Xian Li; Ming Hang Tai; Shuang Song; Hugh Tiang Wah Tan; Ken Leong; Elvis Yew Boon Yip; Grace Yoke Chin Lee; Yanjun Dai; Chi-Hwa Wang (Science of The Total Environment, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Microbial metabolic transformation and antioxidant activity evaluation of polyphenols in kombucha - Shengyang Shi; Yanjun Wei; Xinping Lin; Huipeng Liang; Sufang Zhang; Yingxi Chen; Liang Dong; Chaofan Ji (Food Bioscience, 2023)

Constitutive relation and particle size distribution model of rock fragments in the goaf - Qian Liu; Baiquan Lin; Yan Zhou; Yanjun Li (Environmental Science and Pollution Research, 2023)

The influences of the spatial extent selection for non-landslide samples on statistical-based landslide susceptibility modelling: a case study of Anhui Province in China - Chuhan Wang; Qigen Lin; Leibin Wang; Tong Jiang; Buda Su; Yanjun Wang; Sanjit Kumar Mondal; Jinlong Huang; Ying Wang (Natural Hazards, 2022)

Comparatively analyzing the liver-specific transcriptomic profiles in Kunming mice afflicted with streptozotocin- and natural food-induced type 2 diabetes mellitus - Yanjun Wu; Xiangxing Zhu; Arome Solomon Odiba; Zisheng Lin; Jiancong Wen; Daoyuan Gong; Jing Liang; Shuguang Wu; Ganqiu Lan (Molecular Biology Reports, 2022)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

Spatial Pattern of Female Non-agricultural Employment and Its Driving Forces in Guangdong Province, China: A Perspective of Individual and Family-level - Zhanhui Fu; Lin Mei; Yanjun Liu; Junfeng Tian; Rumin Zheng; Jing Tian (Chinese Geographical Science, 2020)

Faba Bean Organs Differed in Their Effects on Maize Seed Germination Rate and Soil Microbial Activities as well as Their Decomposition Patterns in a Regosol Soil - Zhibin He; Luhua Yao; Xuefeng Zhang; Yang Li; Dengke Wang; Lin Kang; Cui Cui; Aiying Huang; Ruiji Yang; Qianlin Xiao; Yanjun Guo (Journal of Soil Science and Plant Nutrition, 2020)

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

An engineering site suitability index (ESSI) for the evaluation of geological situations based on a multi-factor interaction matrix - Kun Li; Yanjun Shang; Wantong He; Daming Lin; Muhammad Hasan; Kaiyang Wang (Bulletin of Engineering Geology and the Environment, 2019)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

An integrated UAV-borne lidar system for 3D habitat mapping in three forest ecosystems across China - Qinghua Guo; Yanjun Su; Tianyu Hu; Xiaoqian Zhao; Fangfang Wu; Yumei Li; Jin Liu; Linhai Chen; Guangcai Xu; Guanghui Lin; Yi Zheng; Yiqiong Lin; et al. (International Journal of Remote Sensing, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Identification and characterization of a β-1, 3-glucanase gene, TcLr19Glu, involved in wheat resistance against Puccinia triticina - Lin Gao; Shen Wang; Yanjun Zhang; Xiaoying Li; Haiyan Wang; Daqun Liu (Journal of Plant Biochemistry and Biotechnology, 2016)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Modifications to the GSI for granite in drilling - Daming Lin; Yan Sun; Wei Zhang; Renmao Yuan; Wantong He; Bo Wang; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2014)

The rice OsDG2 encoding a glycine-rich protein is involved in the regulation of chloroplast development during early seedling stage - Quan Jiang; XiaoJing Ma; XiaoDi Gong; JianHui Zhang; Sheng Teng; JianLong Xu; DongZhi Lin; YanJun Dong (Plant Cell Reports, 2014)

Deposition rate and interaction of human-riverine from height increase and permanent function of an 1180 years weir in Southeast China - YanJun Shang; Hyeong-Dong Park; ZhiFa Yang; SiGuang Chen; DaMing Lin (Science China Earth Sciences, 2014)

Transcriptional and Functional Studies of a Cd(II)/Pb(II)-Responsive Transcriptional Regulator(CmtR) from Acidithiobacillus ferrooxidans ATCC 23270 - Chunli Zheng; Yanjun Li; Li Nie; Lin Qian; Lu Cai; Jianshe Liu (Current Microbiology, 2012)

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model - Jian Wu; Zhen Peng; Songyu Liu; Yanjun He; Lin Cheng; Fuling Kong; Jie Wang; Gang Lu (Molecular Genetics and Genomics, 2012)

Effect of NaCl on leaf H+-ATPase and the relevance to salt tolerance in two contrasting poplar species - Xiuying Ma; Lin Deng; Jinke Li; Xiaoyang Zhou; Niya Li; Decai Zhang; Yanjun Lu; Ruigang Wang; Jian Sun; Cunfu Lu; Xiaojiang Zheng; Eberhard Fritz; et al. (Trees, 2010)

Molecular Genetic Analysis of QTLs for Ferulic Acid Content in Dried Straw of Rice (Oryza sativa L.) - Yanjun Dong; E. Tsuzuki; H. Kamiunten; Dongzhi Lin; H. Terao; M. Matsuo; Shihua Cheng (Biochemical Genetics, 2005)

Mapping of QTLs for leaf developmental behavior in rice (Oryza sativa L.) - Yanjun Dong; Hiroshi Kamiunten; Tsugufumi Ogawa; Eiji Tsuzuki; Hiroyuki Terao; Dongzhi Lin; Mitsuhiro Matsuo (Euphytica, 2004)

Potential biological control of weeds in rice fields by allelopathy of dwarf lilyturf plants - Dongzhi Lin; Eiji Tsuzuki; Yanjun Dong; H. Terao; T.D. Xuan (BioControl, 2004)